Land cover and climate change threats to savanna and grassland habitats in KwaZulu-Natal - Jewitt, Deborah (My University, 2017)
Global change, specifically land cover change and climate change, are recognised as the leading drivers of biodiversity loss worldwide. Habitat loss has resulted in a loss of biodiversity and led to significant declines in species populations. Climate change is altering species distributions, ecosystem composition and phenology. Conservation planning is required to offset these dynamic threats to species persistence into the future. Plants form the basis of trophic structure and functioning and may not be able to track changing environmental conditions as well as mobile species. They thus represent an essential starting point for understanding climate change and habitat loss impacts. The patterns and processes which generate and maintain floristic diversity must be explored before global change impacts on these communities can be assessed and planned for at a landscape scale. This thesis investigates the environmental variables structuring indigenous plant community composition, pattern and turnover in grassland and savanna systems in KwaZulu-Natal. The threats posed by land cover change and climate change are explored and a coarse-grained landscape connectivity map developed to impart maximum resilience in order to maintain floristic diversity in the era of anthropogenically induced global change. The environmental variables correlated to floristic pattern and turnover were temperature, soil fertility and precipitation variables. The orientation of the temperature gradient conflicts with the soil fertility gradient, hence species with particular soil requirements will be hampered in their efforts to track the temperature gradient. The gradients were non-linear with turnover highest on dystrophic soils in warm and drier summer regions. The major drivers of land cover change were cropped agriculture, timber plantations (agroforestry), rural and urban development, dams and mines. The drivers of change differed according to land tenure type. The average rate of habitat loss in the province over an 18 year period was 1.2% per annum, levels which are considered unsustainable. A target level of 50% of natural habitat remaining is recommended. Environmental domains were identified using the environmental correlates of plant community composition. These were used to investigate climate change impacts using a collection of downscaled climate models. Conditions suiting savanna species are set to increase at the expense of conditions suiting grassland species raising significant challenges for the conservation of grasslands. Indices of habitat intactness and climatic stability were used to develop a vulnerability framework to guide conservation actions to mitigate global change impacts on floristic diversity. Building on the insights gained from the study, a connectivity map linking protected areas was developed, that if implemented, will maximise the opportunity to maintain floristic diversity into the future. The spatial location of the corridors was prioritised based on broad scale climatic refugia, high turnover areas and important plant areas for endemic and threatened species. The corridors were aligned along the major climatic gradients driving floristic pattern. The corridors represent the most natural and cost-effective way for species to adapt to climate change and persist in the landscape. This thesis provides new insights into two global threats facing plant communities in KwaZulu-Natal and provides a suite of products that inform dynamic conservation planning and directs appropriate conservation action. The results may be used to inform policy and legislation.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy The support of the Global Change and Sustainability Research Institute (GCSRI) towards this research is hereby acknowledged. Opinions expressed and conclusions arrived at, are those of the author and are not necessarily to be attributed to the GCSRI. February 2017 in Johannesburg, South Africa
Keywords: Savanna ecology; Land cover--South Africa--KwaZulu-Natal; Climatic change--South Africa--KwaZulu-Natal